Prior exposure to different combinations of pH and undissociated acetic acid can affect the induced resistance of Salmonella spp. strains in mayonnaise stored under refrigeration and the regulation of acid-resistance related genes. (May 2021) - Gavriil, Alkmini; Paramithiotis, Spiros; Skordaki, Asimina; Tsiripov, Eleni; Papaioannou, Adamantia; Skandamis, Panagiotis N.
Abstract: The innate and inducible resistance of six Salmonella strains (4/74, FS8, FS115, P167807, ATCC 13076, WT) in mayonnaise at 5 °C following adaptation to different pH/undissociated acetic acid (UAA) combinations (15mM/pH5.0, 35mM/pH5.5, 45mM/pH6.0) was investigated. The inherent and acid-induced responses were strain-dependent. Two strains (ATCC 13076, WT), albeit not the most resistant innately, exhibited the most prominent adaptive potential. Limited/no adaptability was observed regarding the rest strains, though being more resistant inherently. The individual effect of pH and UAA adaptation in the phenotypic and transcriptomic profiles of ATCC 13076 and WT was further examined. The type (pH, UAA) and magnitude of stress intensity affected their responses. Variations in the type and magnitude of stress intensity also determined the relative gene expression of four genes ( adiA, cadB, rpoS, ompR ) implicated in Salmonella acid resistance mechanisms. adiA and cadB were overexpressed following adaptation to some treatments; rpoS and ompR were downregulated following adaptation to 15mM/pH5.0 and 35mM/pH5.5, respectively. Nonetheless, the transcriptomic profiles did not always correlate with the corresponding phenotypes. In conclusion, strain variations in Salmonella are extensive. The ability of the strains to adapt and induce resistant phenotypes and acid resistance-related genes is affected by the type and magnitude of the stress applied during adaptation. Highlights: Strain dependent inherent and acid adaptive responses of six Salmonella strains Type (pH, UAA) and magnitude of adaptive stress intensity affected induced tolerance Variations in acid adaptive conditions (pH, UAA) affected transcriptomic profiles Phenotypic responses did not always correlate with transcriptomic profiles